Starategi Pemberdayaan Sumber Daya Aparatur Untuk Meningkatkan Kinerja Guna Mewujudkan Good Governance(Kepemerintahan Yang Baik) - Sedarmayanti Sedarmayanti (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
Nowadays, it is time to execute the reformation of civil services in Indonesia, especially in the framework of answering the implementation of the Board Guielines of State Policy in creating good governance and answering the people aspiration on the implementation of clean, transparent and responsible government. The reformation through the functioning was significantly needed in the framework of developing profesionalism, supporting the implementation of regional autonomy and the endeavors of economic recovery.